1999
DOI: 10.1128/aem.65.12.5631-5635.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Bacteriocin-Like Substance Produced by a Vaginal Lactobacillus salivarius Strain

Abstract: A novel bacteriocin-like substance produced by vaginalLactobacillus salivarius subsp. salivarius CRL 1328 with activity against Enterococcus faecalis,Enterococcus faecium, and Neisseria gonorrhoeaewas characterized. The highest level of production of this heat-resistant peptide or protein occurred during the late exponential phase. Its mode of action was shown to be bactericidal. L. salivarius subsp. salivarius CRL 1328 could be used for the design of a probiotic to prevent urogenital infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 22 publications
2
77
0
1
Order By: Relevance
“…Consistent with this hypothesis, Niku-Paavola et al (1999) have proposed that compounds secreted by Lactobacillus plantarum act synergistically with lactic acid, and Makras et al (2006) observed that L. johnsonii NCC533 CFCS was effective against serovar Typhimurium by unknown inhibitory substance(s) that are only active in the presence of lactic acid. These nonlactic acid, heat-resistant anti-Salmonella molecule(s) present in the CFCSs of probiotic Lactobacillus strains have not yet been identified (McGroarty & Reid, 1988;Bernet-Camard et al, 1997;Coconnier et al, 1997;Hudault et al, 1997;Ocana et al, 1999;Aroutcheva et al, 2001b;van de Guchte et al, 2001;Sgouras et al, 2004Sgouras et al, , 2005Fayol-Messaoudi et al, 2005Atassi et al, 2006a). It has already been suggested that pyroglutamic acid may be responsible for the antimicrobial activity of L. rhamnosus GG and L. casei strains LC-10 and LB1931 (Silva et al, 1987;Huttunen et al, 1995;Yang et al, 1997), but it has been found to be intrinsically present in MRS medium and it does not increase during bacterial growth (De Keersmaecker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, Niku-Paavola et al (1999) have proposed that compounds secreted by Lactobacillus plantarum act synergistically with lactic acid, and Makras et al (2006) observed that L. johnsonii NCC533 CFCS was effective against serovar Typhimurium by unknown inhibitory substance(s) that are only active in the presence of lactic acid. These nonlactic acid, heat-resistant anti-Salmonella molecule(s) present in the CFCSs of probiotic Lactobacillus strains have not yet been identified (McGroarty & Reid, 1988;Bernet-Camard et al, 1997;Coconnier et al, 1997;Hudault et al, 1997;Ocana et al, 1999;Aroutcheva et al, 2001b;van de Guchte et al, 2001;Sgouras et al, 2004Sgouras et al, , 2005Fayol-Messaoudi et al, 2005Atassi et al, 2006a). It has already been suggested that pyroglutamic acid may be responsible for the antimicrobial activity of L. rhamnosus GG and L. casei strains LC-10 and LB1931 (Silva et al, 1987;Huttunen et al, 1995;Yang et al, 1997), but it has been found to be intrinsically present in MRS medium and it does not increase during bacterial growth (De Keersmaecker et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of pathogen growth is a property often displayed by lactic acid strains (Vandenbergh 1993). Pathogen growth has been found to be inhibited as the result of the production of inhibiting factors by Lactobacillus strains, including bacteriocin-like substances, hydrogen peroxide and/or nonbacteriocin, nonlactic acid molecules (McGroarty and Reid 1988;Klebanoff et al 1991;Ocana et al 1999;Aroutcheva et al 2001;van de Guchte et al 2001). The data show that after direct co-culture with L. helveticus strain KS300 the viability of vaginosis-associated G. vaginalis, P. bivia, diarrhoeagenic S. typhimurium, and uropathogenic Dr-positive E. coli was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has isolated and identified lactic acid bacteria from women in San Miguel de Tucum an (Argentina) (Ocaña et al 1999a;Ju arez Tom as et al 2011) and evaluated their beneficial properties that include the production of antimicrobial substances (lactic acid, hydrogen peroxide and bacteriocins) (Ocaña et al 1999b(Ocaña et al , 1999c(Ocaña et al , 1999dVera Pingitore et al 2009;Ju arez Tom as et al 2011;Nader-Mac ıas and Ju arez-Tom as 2015), biofilm formation (Leccese Terraf et al 2016Terraf et al , 2017, inhibition of urogenital pathogens (e.g. Candida albicans, Streptococcus agalactiae, Escherichia coli, Staphylococcus aureus), modulation of the immune system and protection against pathogens in experimental murine model (De Gregorio et al 2014; Nader-Mac ıas and Ju arez-Tom as 2015; De Gregorio et al 2016;De Gregorio et al 2019).…”
Section: Introductionmentioning
confidence: 99%